Pengaruh Corporate Governance terhadap Kemungkinan Kecurangan Laporan Keuangan: Studi Empiris pada Perusahaan BUMN Tahun 2018-2021 - Nofenti Marlinda; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2024)
This research aims to determine the influence of corporate governance on the possibility of fraudulent financial reports in state-owned companies in 2018-2021. This type of research is causative research with a quantitative approach. This type of research data uses secondary data. Secondary data was obtained from the official website of BUMN companies. The sample used in this research was 26 companies with data for 2018,2019, 2020 and 2021. The sample in this research was 21 companies. Researchers used logistic regression analysis. The results of this research indicate that managerial ownership, board of commissioners, audit committee and institutional ownership have no effect on the possibility of financial statement fraud.